Trends of climate change at the mid-low Nazas-Aguanaval inland basin based on a geographical approach - Villegas, Omag Cano; Muro-Pérez, Gisela; Jurado, Enrique; Flores, Joel; Castañeda-Gaytan, José Gamaliel; Aguirre, Oscar; Sánchez, Jaime (Ecosistemas y Recursos Agropecuarios, 2021)
An integrative geographical climatology is presented to objectively identify regional patterns of climate variability within the mid-low Nazas-Aguanaval basin within the States of Durango and Coahuila in Central Northern Mexico, using decadal mean values for maximum and minimum temperature, as well as monthly precipitation during the seven periods from 1951-2020. The historical data was acquired from 26 field meteorological stations and 44 grid points from the SWAT model. Furthermore, the data was categorized by means of geographical features of altitude, longitude and latitude in three groups each. A combination of meteorological vulnerability from all the categories for each sampling point was then estimated for each locality. From the overall analysis, western sites resulted as the most vulnerable to climatic changes, while eastern and central (latitude) displayed the lowest variability occurrence. By means of downscaling the meteorological variation, it is possible to improve the understanding of mechanisms relying on regional climate variability and climate change. This evaluation can be further incorporated to management strategies for different stakeholders in arid and semi-arid lands, particularly within the Chihuahuan Desert.
Keywords: Meteorological trends; Aridlands; Regionalization; Climate change; Geography.